Mengungkap Pola Aset Rusak Berat/Hilang pada Laporan Keuangan Pemerintah Daerah Provinsi Sulawesi Tengah - Muwahhidin Muwahhidin; Maya Al Zahra; Ismail Ismail; Nina Yusnita Yamin; Selmita Paranoan; Betty Betty (Journal of Applied Accounting, 2026)
This study aims to analyze the growth pattern of severely damaged and lost assets presented in the Local Government Financial Statements (LKPD) of Central Sulawesi Province during 2020–2024 as an indication of delays in the asset disposal process. The study employed a quantitative approach using descriptive-analytical methods. Data were collected through documentation of LKPD, Notes to Financial Statements (CaLK), and supporting documents related to regional asset conditions. Data analysis was conducted using Growth Analysis to identify annual changes in the value of severely damaged and lost assets. The results indicate substantial fluctuations during the observation period. The largest decline occurred in 2022 at 28.66%, mainly driven by large-scale asset disposals, while the largest increase occurred in 2023 at 34.71%, due to asset reclassifications, inter-agency asset transfers, and recognition of extracomptable assets. These fluctuations suggest that asset disposal activities have not been implemented consistently and promptly. Consequently, severely damaged and lost assets remained recorded for extended periods, creating a risk of asset overstatement in financial reporting. The findings also reflect weaknesses in asset administration, asset verification, and internal control over regional asset management. Therefore, strengthening asset governance and improving the effectiveness of asset disposal procedures are necessary to enhance the reliability and accountability of local government financial reporting. Keywords: Asset Management, Asset Disposal, Severely Damaged Assets, Lost Assets, Accountability.